2021
DOI: 10.1101/2021.10.16.464662
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The power of peer networking for improving STEM faculty job applications: a successful pilot program

Abstract: In order to successfully obtain a faculty position, postdoctoral fellows or postdocs, must submit an application which requires considerable time and effort to produce. These job applications are often reviewed by mentors and colleagues, but rarely are postdocs offered the opportunity to solicit feedback multiple times from reviewers with the same breadth of expertise often found on an academic search committee. To address this gap, this manuscript describes an international peer reviewing program for small gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…It has been suggested that interactions with their research advisor exerts the highest influence amongst the experiences of research trainees (Barnes and Austin, 2009; Lovitts, 2001; Sverdlik et al, 2018; Zhao et al, 2007). This single mentor model may be complemented by a variety of mentorship formats, such as mentoring networks (e.g., principal investigators of collaborating labs for postdoctoral researchers or thesis committees for graduate students), peer-mentoring, group mentoring, or distance mentoring, which can occur on an informal or formal basis (Bielczyk et al, 2019; Guardia et al, 2021; Lorenzetti et al, 2019; Sarabipour et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that interactions with their research advisor exerts the highest influence amongst the experiences of research trainees (Barnes and Austin, 2009; Lovitts, 2001; Sverdlik et al, 2018; Zhao et al, 2007). This single mentor model may be complemented by a variety of mentorship formats, such as mentoring networks (e.g., principal investigators of collaborating labs for postdoctoral researchers or thesis committees for graduate students), peer-mentoring, group mentoring, or distance mentoring, which can occur on an informal or formal basis (Bielczyk et al, 2019; Guardia et al, 2021; Lorenzetti et al, 2019; Sarabipour et al, 2021).…”
Section: Introductionmentioning
confidence: 99%